Perspectives on teaching performance after COVID-19 - Cuellar-Quispe, Sergio; Huaman-Romani, Yersi-Luis; Sarmiento-Campos, Noemi-Victoria; Silvera-Alarcon, Edwin-Neil; Nolasco-Carbajal, Elio (International Journal of Innovative Research and Scientific Studies, 2023)
The evaluation of a teacher's performance is conducted subjectively rather than objectively to determine the students' educational experience and the demands placed on them by the university which provides teachers with a backup plan. The objective of this research is to analyze and describe the perspectives on teaching performance after COVID-19. A conventional, anonymous and voluntary sample of 2263 university students from state and private universities was used in the quantitative approach of a descriptive correlational type. Teaching performance was assessed using a questionnaire with 20 items that were divided into five categories: explanation of criteria, illustration, supervision of practice and learning activities, feedback and evaluation. The findings of the research show that there is good virtual teaching performance. The university teacher shows that they are able to teach in a hybrid way. A Cronbach's alpha of 0.946 was obtained and several statistical tests were performed such as total mean (3.733), standard deviation (1.064), ANOVA with Turkey's non-additivity test (sum of squares 81.102, gl=19, F=12. 035), Hoteling’s t-squared test (283.464, F=14.800, Sig. 0.000), KMO and Bartlett's test (KMO=0.977), Bartlett's test of sphericity with chi-square 52808.872, gl=190, Sig. 0.000. University professors demonstrated a good teaching performance in front of students, having empathy with their students and managing to place themselves among people with digital competences and within the society of the digital world.